Comparison of Reverse Osmosis and Non Reverse Osmosis Disinfection Methods for Drinking Water Depot - Muhamad Iqbal; Ruslan La Ane (Faculty of Public Health, Hasanuddin University, Makassar, 2022)
Drinking Water Depot (DWP) offers cheap and affordable drinking water, so it becomes an option for the society. However, the large number of public interest is not accompanied by qualified water quality. The test result by Bandung Public Health Office on DWP quality indicated that 55.22% were not eligible. The study aimed to determine the effective disinfection method to reduce microbiology in Reverse Osmosis (RO) and Non-RO methods. It was an analysis with a cross-sectional design. The population was all DWPs in Bandung and obtained 659 DWPs as samples. Sampling used two different tests and obtained 30 samples consisting of 30 DWP using RO and 30 Non-RO in average. Data analysis was done through univariate and bivariate using Wilcoxon Rank Sum test. The analysis result showed that polluted water raw quality was 48.33%; the bacteria reduction by RO method was 100% and Non-RO was 43.33%. The bivariate analysis result indicated that p-value was 0.033 which means that there was a difference between disinfection method using RO and Non-RO with the coliform presence. The RO disinfection is the best method which was able to be used by DWP owners. Thus, the society is suggested to choose DWP using RO disinfection method which verified by Public Health Department.